Work – Family Conflict as Correlate of Burnout Among Married Female Bank Workers - Ozor, Tobias Obiora (Practicum Psychologia, 2018)
This study investigated Work–Family Conflict (WFC) as correlate of Burnout among married female bank workers. 321 (three hundred and twenty-one participants (female bankers) randomly drawn from five banks in Enugu State of Nigeria participated in the study. Two instruments used in collecting data were subscales of Maslach and Jackson (1986) Burnout Inventory and Okonkwo (2011) Work-Family Conflict Scale. The study adopted a Correlational design and pearson r Correlation coefficient was used to analyze the data collected. The results indicated a no significant correlation between global WFC and Burnout (p>.05). However, Both WFC and its’ sub scales (Time Base “TB” & Behavior Base “BB”) significantly and positively correlated with Depersonalization and Emotional Exhaustion at p = .05.Thus, as WFC increases there is also an increase in Depersonalization and Emotional Exhaustion components of Burnout. The discussion, limitations and implications of the study was made based on the findings.